(x/5)=4+(x-6)/3

Simple and best practice solution for (x/5)=4+(x-6)/3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x/5)=4+(x-6)/3 equation:



(x/5)=4+(x-6)/3
We move all terms to the left:
(x/5)-(4+(x-6)/3)=0
We add all the numbers together, and all the variables
(+x/5)-(4+(x-6)/3)=0
We get rid of parentheses
x/5-(4+(x-6)/3)=0
We calculate fractions
3x^2/()+(-(4+(x-6)*5)/()=0
We calculate terms in parentheses: +(-(4+(x-6)*5)/(), so:
-(4+(x-6)*5)/(
We multiply all the terms by the denominator
-(4+(x-6)*5)
We calculate terms in parentheses: -(4+(x-6)*5), so:
4+(x-6)*5
determiningTheFunctionDomain (x-6)*5+4
We multiply parentheses
5x-30+4
We add all the numbers together, and all the variables
5x-26
Back to the equation:
-(5x-26)
We get rid of parentheses
-5x+26
Back to the equation:
+(-5x+26)
We get rid of parentheses
3x^2/()-5x+26=0
We multiply all the terms by the denominator
3x^2-5x*()+26*()=0
We add all the numbers together, and all the variables
3x^2-5x*()=0

See similar equations:

| (3x-4)^3-125=0 | | 1/4-10x=-50 | | 167=-112-x | | 3x-9=-×+15 | | 2a-9=38 | | .1t+.6(30-t)=7.5 | | 9-x-7x=-39 | | 4^x-3=3x-8 | | 3x+21=14 | | 6/7=1/7+5/4a | | -3x+4x=-5–6x | | 6x^2-14=76 | | x+.2x=177000 | | 6/7=1/7=5/4a | | n-8/3=1 | | -3(N+1)-n-10=-4(n+5)+7 | | 7/y-7/y-8-8=0 | | z^2-5z-45=0 | | x-14/2=13 | | -11-8+3y=24 | | 5/z=2/z+3 | | 1m-6=-12 | | 9-9+p-4=-4 | | 19−6(−k+4)=0 | | 4.5p=6.1 | | 24k-24=-5k-32 | | 72-7x=5x-12 | | x+.2x=190000 | | 3(k-2)-7=4K-(3k-1) | | 9|-9+p|-4=-4 | | 9y=72+y | | 24k-24=-5-32 |

Equations solver categories